In search of lost time: investigating the temporality of student engagement, the role of learning technologies, and implications for student performance - O Riordan, Niamh (ACIS, 2014)
Much has been written about the importance of engaging students in the learning process. However, studies have shown that students today spend significantly less time on their studies than their forebears. Given the limitations of the existing body of knowledge, this study reviews what is currently known about full-time college students’ time use and its consequences in terms of exam performance and skill acquisition. In particular, the results of our initial investigation suggest the ubiquity of today’s technologies, especially the Internet, has significant and frequently overlooked consequences for student engagement in general and for their consumption of content for learning in particular. Further, future studies are needed to unravel the complex relationship that exists between learning technologies, students’ time use and their academic performance. The paper concludes by highlighting a number of possible avenues for future research in this area.